2017
DOI: 10.1016/j.heares.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus and hyperacusis: Contributions of paraflocculus, reticular formation and stress

Abstract: Tinnitus and hyperacusis are common and potentially serious hearing disorders associated with noise-, age- or drug-induced hearing loss. Accumulating evidence suggests that tinnitus and hyperacusis are linked to excessive neural activity in a distributed brain network that not only includes the central auditory pathway, but also brain regions involved in arousal, emotion, stress and motor control. Here we examine electrophysiological changes in two novel non-auditory areas implicated in tinnitus and hyperacusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 97 publications
1
14
0
Order By: Relevance
“…After auditory nerve transection, the phantom experience of tinnitus still does not disappear (Jackler and Whinney, 2001 ). It has been demonstrated that tinnitus involves aberrant neural activity in not only auditory regions but also non-auditory structures such as the prefrontal cortex, parahippocampal gyrus (PHG), amygdala, and cerebellum, which have been confirmed to be important in the development or progression of tinnitus (Rauschecker et al, 2010 ; Leaver et al, 2011 ; Langguth et al, 2013 ; Chen et al, 2015a , 2017a , b , c ; Brozoski et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…After auditory nerve transection, the phantom experience of tinnitus still does not disappear (Jackler and Whinney, 2001 ). It has been demonstrated that tinnitus involves aberrant neural activity in not only auditory regions but also non-auditory structures such as the prefrontal cortex, parahippocampal gyrus (PHG), amygdala, and cerebellum, which have been confirmed to be important in the development or progression of tinnitus (Rauschecker et al, 2010 ; Leaver et al, 2011 ; Langguth et al, 2013 ; Chen et al, 2015a , 2017a , b , c ; Brozoski et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperacusis is also associated with anxiety, depression, schizophrenia and sleep disorders [ 3 , 15 , 16 ]. Approximately 40% of patients with tinnitus also suffer from hyperacusis whereas up to 80% of patients with hyperacusis also have tinnitus, suggesting that these disorders may share a common pathophysiology [ 8 , 9 , 17 ]. While hyperacusis and tinnitus are often associated with hearing loss [ 18 20 ], some individuals with hyperacusis and/or tinnitus have clinically normal audiograms [ 15 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have focused on the association between hyperacusis and tinnitus [ 8 , 9 , 17 20 , 42 44 ]; however, much less is known about the association between hyperacusis and somatic tinnitus, although the former has been shown to be associated with disordered perceptions involving the somatosensory domain. Some report an increased prevalence of hyperacusis in somatic tinnitus patients [ 45 ] while others have not [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increased prevalence of somatic modulation found by the authors in hyperacusis patients could be due to increased peripheral somatic activation or central hypersensitivity to somatic inputs. The latter is supported by neurophysiological findings that show increased sensitivity to multisensory stimuli in patients with hyperacusis, which may be linked to a hypervigilance network [80][81][82][83][84] . Also, Schecklmann 79 and Gilles 85 found worse tinnitus and depression scores in patients with hyperacusis than in those without.…”
Section: Schecklmannmentioning
confidence: 71%